Kids in the Wind - Wethern, Brad, 1942- (Book collections on Project MUSE., 2015)
"These seven short stories trace the childhood memories of a young boy, humorously nicknamed General Custer. The General, optimistic by nature and battered by circumstances, moves from Corvallis, Oregon, to the coastal town of Fairhaven, California. In this patchwork tarpaper town, on the north spit of Humboldt Bay, there are no phones, no indoor toilets, and with mostly absent parents, very few rules for rugged country kids. Tracing General Custer's intrepid spirit and ardent observations, Kids in the Wind brims with windy salt air, unimaginable adventure, embarrassing discoveries of young love, and a great deal of humor. As the stories unravel they lead you to that age-old-question-why grow up? "--